Incidence of Post-Traumatic Stress Disorder After Road Traffic Accident - Fekadu, Wubalem; Mekonen, Tesfa; Belete, Habte; Belete, Amsalu; Yohannes, Kalkidan (Frontiers in Psychiatry, 2019)
Background: Post-traumatic stress disorder (PTSD) occurs after exposure to actual or threatened death, serious injury, or sexual violence. Road Traffic Accident (RTA) is one of the traumatic experiences, which may result in post-traumatic stress disorder. But, treatment is mainly concentrated on physical health. This may be due to a lack of evidence in low-income countries. Aim: To determine the incidence level and identify risk factors of Post-Traumatic Stress Disorder (PTSD) after RTA. Methods: Longitudinal panel study was done to assess the incidence of PTSD after RTA. The study was conducted in three orthopedic settings of Bahir Dar town Northwest, Ethiopia. The study was on 299 adult car accident survivors. PTSD Checklist (PCL) civilian version, Sheehan disability assessment scale, Patient Health Question (PHQ -2) and Alcohol Use Disorder Identification Test (AUDIT) were instruments to assess the outcome and associated factors. The generalized linear model with Poisson log-linear method was applied to identify associated factors. Ethical clearance was obtained from Bahir Dar University. Individuals with PTSD symptoms were linked to the psychiatric clinic. Result: One hundred thirty-nine (46.5%) participants had at least three extremely severe symptoms which fulfill criteria B, C and D of Diagnostic Statistical Manual IV of PTSD. The most frequent severe symptoms were having repeated, disturbing memories, thoughts, or images. Two hundred ten (70.2%) participants reported the extreme impact of the accident on work or schooling and 156(51.9%) report extreme problems in social functioning. Alcohol dependence, hazardous alcohol consumption, and harmful use were reported by 7.9%, 15.1% and 4.7% of the participants respectively. In the final model witnessing death, severe sleep problem and severe impairment in family functioning were significantly associated with PTSD. Conclusion: Nearly half of RTA survivors develop PTSD. Clinicians need to link these patients to the psychiatry clinic. Special attention should be given to patients who witnessed death, with a serious disability and previous psychiatric history.